2020
DOI: 10.1111/os.12768
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Superior Capsule Reconstruction and Rotator Cuff Repair to Restore Static and Dynamic Stability of the Shoulder

Abstract: Objective: Treatment of massive irreparable rotator cuff tears (RCT) has shown limited clinical success and a variety of subsequent complications. Superior capsule reconstruction (SCR) has been proved to reestablish superior stability but does not restore the dynamic force or shoulder kinematics. There are numerous reports of the short-term failure of SCR grafts at the glenoid side, which relate to the non-biological healing of grafts. To restore both dynamic and static stability and to provide biologic augmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…In addition, a previous cadaveric biomechanical study 47 has suggested that repair of the ASCR graft with posterior or anterior rotator cuff tissue could increase the AHD postoperatively by decreasing the glenohumeral superior translation. ( Fig 5 ) Furthermore, posterior or anterior margin convergence may increase the survival rate of graft by accelerating the vascularization, 51 which reinforced the structural strength of the graft as well.
Fig 5 Posterior margin convergence may increase the postoperative acromiohumeral distance (AHD) postoperatively by decreasing the glenohumeral superior translation.
…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous cadaveric biomechanical study 47 has suggested that repair of the ASCR graft with posterior or anterior rotator cuff tissue could increase the AHD postoperatively by decreasing the glenohumeral superior translation. ( Fig 5 ) Furthermore, posterior or anterior margin convergence may increase the survival rate of graft by accelerating the vascularization, 51 which reinforced the structural strength of the graft as well.
Fig 5 Posterior margin convergence may increase the postoperative acromiohumeral distance (AHD) postoperatively by decreasing the glenohumeral superior translation.
…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the material selection of ligament reconstruction includes autografts, allografts, and synthetic materials 6 , 15 , 16 . Based on the fact that different grafts have their own advantages, the selection of grafts was mainly based on individual needs and surgeons' experience.…”
Section: Discussionmentioning
confidence: 99%
“…Авторы сообщали о благоприятных результатах, а именно о снижении болевого синдрома и увеличении объема движений поврежденного сустава, однако в 16,7% случаев были отмечены отрывы трансплантата, частота которых, по данным литературы, составляет от 10 до 12,9%. Описаны также случаи повторных проксимальных подвывихов головки плечевой кости в результате растяжения трансплантата и последующего его отрыва [5][6][7].…”
Section: Discussionunclassified